2014
DOI: 10.1162/comj_a_00229
|View full text |Cite
|
Sign up to set email alerts
|

Free as in BEER: Some Explorations into Structured Improvisation Using Networked Live-Coding Systems

Abstract: Much improvised music that has developed since the advent of free jazz has been concerned with the imposition of structure, often through systems of directed improvisation, or through the use of rule-based approaches (e.g., game pieces). In this article, we explore the possibility of a networked live-coding system as a structural intervention mechanism par excellence, through the discussion of two pieces from the repertoire of the Birmingham Ensemble for Electroacoustic Research.The relationship between live c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In BEER's Pea Stew continuous audio signals (sent with jacktrip) are recirculated around a network of performers, with FFT-based phase shift as well as other live-coded transformations applied at each node. In another BEER piece, Telepathic, the network is used to share parameters -establishing a shifting, centralized tempo as well as quantizing the redefinition of three different musical layers by individual live-coding ensemble members, so as to produce unified, drastic changes in the resulting texture (Wilson et al 2014).…”
Section: Bandwidthmentioning
confidence: 99%
“…In BEER's Pea Stew continuous audio signals (sent with jacktrip) are recirculated around a network of performers, with FFT-based phase shift as well as other live-coded transformations applied at each node. In another BEER piece, Telepathic, the network is used to share parameters -establishing a shifting, centralized tempo as well as quantizing the redefinition of three different musical layers by individual live-coding ensemble members, so as to produce unified, drastic changes in the resulting texture (Wilson et al 2014).…”
Section: Bandwidthmentioning
confidence: 99%
“…It's Turing complete so in theory anything can happen but in practice it's probably quite a limited exploration. (McLean 2013, 35:16) Others emphasise different aspects of live coding, such as providing alternatives to conventional means of expression (Wilson et al 2014); improvisation in computer music (McCallum 2011, 2 minutes); the hazards of performance (McLean et al 2004), and accessibility (McLean et al 2004) Some more negative aspects have been identified as well, for instance 'the corporeal difference between direct control of a physical instrument and indirect control via program code,' (Collins and Brown 2009, p. 2) and the 'computer head' problem during performance where the performers are, heads down inside their laptops, significantly less animated than the audience (McLean 2013).…”
Section: Live Codingmentioning
confidence: 99%
“…This had an immediate impact on composition and performance because it highlighted the potential loss of causal logic and lack of expression 13 when performers' gestures cannot be associated with sonic outputs. 17 Concerns with mapping, metaphor and transparency are conspicuous in the literature and practice of physical gestural controllers 18 and have also influenced less obvious areas such as live coding: for instance, in the case of Pea Soup, by BEER, 19 a strong metaphor emerges of performers shaping the constituents of a single sonic entity passed around between them by means of a network, as if they were all sculpting a big common object (Wilson, Lorway, Coull, Vasilakos and Moyers 2014). 17 Concerns with mapping, metaphor and transparency are conspicuous in the literature and practice of physical gestural controllers 18 and have also influenced less obvious areas such as live coding: for instance, in the case of Pea Soup, by BEER, 19 a strong metaphor emerges of performers shaping the constituents of a single sonic entity passed around between them by means of a network, as if they were all sculpting a big common object (Wilson, Lorway, Coull, Vasilakos and Moyers 2014).…”
Section: Decoupling Of Sound Control From Sound Productionmentioning
confidence: 99%
“…Concerns with mapping, metaphor and transparency are conspicuous in the literature and practice of physical gestural controllers 18 and have also influenced less obvious areas such as live coding: for instance, in the case of Pea Soup , by BEER, 19 a strong metaphor emerges of performers shaping the constituents of a single sonic entity passed around between them by means of a network, as if they were all sculpting a big common object (Wilson, Lorway, Coull, Vasilakos and Moyers 2014).…”
Section: Musicmentioning
confidence: 99%